SMEs’ Internationalization Strategy in Export Creative Industry: Case Study from Kendang Djembe Creators at Blitar, East Java, Indonesia - Meldona, Meldona; Sudarmiatin, Sudarmiatin; Bidin, Rosmiza (CV. Inara, 2022)
This study aims to: (a) describe the internationalization strategy of SMEs in the export-oriented creative industry of Kendang Djembe, Blitar, (b) identify the strengths, weaknesses, opportunities and threaths of the internationalization process of the export-oriented creative industries of SMEs, especially in the Kendang Djembe industry in Blitar, East Java. Indonesia. The approach used in this study is a SWOT analysis with an internal-external matrix (IFAS & EFAS) to 4 SMEs, which are 10 key informants of exportir Kendang Djembe in Blitar. The results show that Kendang Djembe Creative Industry SMEs in Blitar have good strengths and opportunities in improving their international processes. Based on internal and external factors, these SMEs are in a growth position (in caution condition). Thus, the suitable internationalization strategy to be developed are the SO, ST, WO and WT strategy, that are: adding online marketing networks (or other collectors), diversifying products beyond the main product, optimizing the role of associations related to product delivery cooperation, improving technology skills through training or independently learning and lobbying the government regarding the ease of export policies conditions.